Results of the trawl survey of nekton and macroplankton during preanadromous migrations of pacific salmon in the North-West Pacific in 2023 - A. N. Starovoytov (Известия ТИНРО)
Results of the trawl survey in the Pacific waters at Kuril Islands within and outside EEZ of Russia conducted by RV TINRO in June-July 2023 are analyzed. Data on spatial distribution, abundance and biomass of fish, cephalopod and jellyfish species in the epipelagic layer are presented. Contemporary status of the epipelagic nekton community in the surveyed area is analyzed. Quantitative distribution and biological state of pink salmon and other species of salmon in the summer season are considered in details.